Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan PT Plasindo Lestari - Muhammad Ari Setiawan; Syifa Pramudita (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Based on research observations regarding the effect of job training, work discipline on employee performance simultaneously this variable affects employee productivity which has direct implications for performance. appreciation and decreased productivity due to lack of competence so that as a solution companies can apply diversity leadership and leadership ethics in order to build a good organizational culture by postponing collaboration and increasing competence through regular training.